Religion and the obligations of citizenship - Weithman, Paul J (Cambridge University, 2013)
In Religion and the Obligations of Citizenship, Paul J. Weithman asks whether citizens in a liberal democracy may base their votes and their public political arguments on their religious beliefs. Drawing on empirical studies of how religion actually functions in politics, he challenges the standard view that citizens who rely on religious reasons must be prepared to make good their arguments by appealing to reasons